Flight Test Intelligent Mission Planning System Based on Big Data Platform - Zeyuan, He; Huahui, Wang; Nanbo, Li (2021 IEEE International Conference on Electronic Technology, Communication and Information (ICETCI), 2021)
In order to improve the capability of aircraft flight test data, this paper proposes an intelligent flight test mission planning system which is based on a big data platform, combined with artificial intelligence algorithms, modeling and simulation technologies. This system can meet the flight test requirements of the new aircraft, and complete the test flight syllabus, decompose and integrate the test flight task, make the test flight plan for the specific sortie and verify the simulation. Finally, it can formulate a scientific and efficient test flight plan. The intelligence of the system runs through the entire workflow, including the design, validation and finalization of the flight test plan. This article will introduce the main principles and methods of this system.